Standard and water rehabilitation: An analysis of over 14 years' experience in patients with haemophilia or other clotting factor disorders after orthopaedic surgery. Issue 4 (17th April 2019) - Passeri, E.V.; Martinelli, Marco; Gatteri, Vincenzo; Pivetti, Stefania; Passeri, Chiara; Cigolini, Luisa; Chiari, Sonia; Zenorini, Andrea; Gaffurini, Paolo; Bernardi, Stefano; Poli, Ilaria; Bissolotti, Luciano
Abstract : Introduction: In people with haemophilia (PWH) with severe arthropathy, total joint replacement (TJR) can be undertaken if conservative management fails. Post‐operative rehabilitation treatment is an important part of the comprehensive management of patients undergoing TJR. Aim: To compare post‐operative standard rehabilitation (SR) and SR plus water rehabilitation (WR) in PWH undergoing TJR. Methods: PWH who were admitted to our centre between June 2003 and December 2016 for rehabilitation after TJR were included in the study. Rehabilitation included SR (ie, manual and mechanical mobilization, scar tissue massage, light muscle strengthening exercises and walking training with and without crutches) with or without WR. WR exercises with floats of different size and volume were performed when possible. Range of motion (ROM), muscle strength, pain level, perceived health status and length of hospital stay were analysed retrospectively. Results: A total of 184 patients (233 rehabilitation programmes were enrolled in the study, corresponding to 160 after total knee replacement [TKR], 37 after total ankle replacement [TAR] and 36 after total hip replacement [THR]). Fifty‐eight (25%) patients were treated with WR in addition to SR (32 for TKR, 19 for TAR and 7 for THR) with an average of 5.7 hours of WR. Muscle strength, pain and perceived health status improved significantly after rehabilitation. Conclusion: This non‐randomized study seems to indicate that WR plus SR improves muscle strength, pain and perceived health status more than SR alone in PWH undergoing TJR. It would be necessary, however, to carry out randomized comparative studies to confirm these provisional conclusions.